Glucose Response after a Ten-Week Training in Swimming - Sengoku, Y.; Nakamura, K.; Takeda, T.; Nabekura, Y.; Tsubakimoto, S. (International Journal of Sports Medicine, 2011)
The present study investigated the difference in blood glucose concentration (Glu) response during an incremental swimming test before and after a ten-week training period and verified whether blood glucose threshold (GT) could be determined in competitive swimmers. 7 elite male university swimmers participated in this study. 2 incremental swimming tests were conducted in a swimming flume before and after a ten-week training period. Blood lactate concentration (Bla) and Glu were measured after each swimming step, and the velocities of the lactate threshold (VLT) and glucose threshold (VGT) were analyzed. VLT increased significantly after training (1.21±0.06 m·s−1 pre-training, 1.31±0.10 m·s−1 post-training, p<0.05), while Glu did not increase at the higher swimming intensity steps. GT was not determined at each trial. Our results show that lactate threshold (LT) improved significantly after the ten-week training period, while the Glu response during incremental swimming tests did not change. Therefore, GT could not be determined in elite competitive swimmers before and after training.
Keywords: endurance capacity; anaerobic threshold; metabolic response